Blindness, Judicial Blinding, and Social Death in Early Modern Germany - Baum, Jacob M. (Renaissance and Reformation / Renaissance et Réforme, 2025)
This article examines the great age of corporal punishments in German-speaking lands to draw attention to the historical intersections between senses, disability, and social death. Between approximately 1400 and 1550, civic and territorial magistrates administered a wide variety of corporal punishments on subjects, including mutilating punishments such as blinding. This article sketches the history of judicial blinding through a close reading of the archival record from the free imperial city of Frankfurt am Main and contextualizes this evidence by reference to the practice in other sites across German-speaking lands. It explains the origins of judicial blinding, analyzes major patterns in how the punishment was administered, and interprets the age of judicial blinding as a long experiment in social death. To make this final interpretive argument, this article shows how those who suffered the punishment embodied the three major criteria associated with social death in modern theoretical discussions of the concept: loss of bodily integrity, loss of social identity, and loss of social networks. Throughout, analysis and interpretation bring together insights from early modern sensory history and disability history.